Implementasi Desentralisasi Composting melalui Pendampingan Pokdarwis Permata Pilang dalam pembuatan Kompos Organik dengan Memanfaatkan Limbah Kotoran Sapi di Pasar Hewan Wonoasih dan Sampah Daun Kering PT. Kutai Timber Indonesia Kota Probolinggo - Agus Setiawan; Arbie Suwandana Putra; Ifani Mulya Agustianingsih (LPPM Universitas Yudharta Pasuruan, 2020)
Various ways and efforts to reduce waste continue to be carried out by multiple parties, especially in managing organic waste in Probolinggo. Through the Community Development approach, the result of this devotion can build multi-party synergy between the Probolinggo City Environment Office, Permata Pilang Tourism Awareness Group, Wonoasih Animal Market Manager, and PT. Kutai Timber Indonesia reduces cow dung's organic waste to organic compost through Permata Pilang organic compost house. Activities by accompanying Pokdarwis as the main driver in managing organic compost with the support of various parties have reduced cow dung waste from Wonoasih Animal Market by 12 Tons/month and dry leaf waste from PT. Kutai Timber Indonesia becomes an independent product of organic compost fertilizer to support agriculture in Probolinggo City. This assistance also impacts opening new jobs for Pokdarwis Permata Pilang youth with a turnover value of 9 million / month and building multi-party synergies to implement decentralized composting in Probolinggo City.